Lipid-mediated lysozyme aggregation: furster resonance energy transfer study - Trusova, V.M. (Харьковский Национальный Университет им. В.Н.Каразина, 2010)
Aggregation of proteins into insoluble complexes is intimately linked to pathogenesis of several neurodegenerative diseases. Protein aggregation is commonly regarded as nonspecific coagulation of incompletely folded or partially denaturated polypeptides, driven by interaction between the exposed hydrophobic patches. Accumulating evidence indicates that protein self-association can be induced by protein-lipid interactions. The present study addresses a problem of aggregation behavior of lysozyme (Lz) bound to model membranes composed of phosphatidylcholine (PC) and phosphatidylglycerol (PG) (8:2). The formation of Lz assemblies in lipid environment has been monitored by measuring steady-state resonance energy transfer (FRET). Several donor-acceptor pairs have been employed: tryptophan (Trp) – pyrene, pyrene – fluorescein 5’-isothiocyanate (FITC) and FITC – rhodamine-isothiocyanate (RITC). Fluorescence spectra of pyrene maleimide-labelled Lz (Lz-PM) recorded at different lipid-to-protein molar ratios (L:P) with excitation wavelength of 296 nm were featured by three bands corresponding to Trp, pyrene monomer and excimer emission. Analysis of the shape of emission spectra showed that the ratio of PM to Trp intensity rises with increasing Lz-PM concentration and decreasing L:P values from 379 to 77. This effect is most probably to arise from the enhanced FRET between Trp and pyrene. The finding that the magnitude of this effect depends on protein concentration suggests that FRET enhancement is caused by the formation of protein aggregates. The same result was obtained with Lz- attached pyrene as donor and Lz-attached FITC as acceptor – the efficiency of energy transfer increased with increasing total protein concentration and decreasing L:P. Notably, the most pronounced increase of energy transfer efficiency was observed at surface coverage ca. 38 lipids per one protein molecule suggesting that this L:P value is critical for formation of Lz self-associates. The assumption that Lz forms aggregates in membrane environment is also corroborated by the quantitative analysis of FRET between FITC and RITC. The distance between FITC and RITC was found to be ca. 8 nm which exceeds the dimensions of Lz molecule by 2-2.5 times, lending additional support to the idea about Lz self- association in lipid surroundings.
Keywords: lysozyme; lipid bilayer; aggregation; Furster resonance energy transfer